ISOLATION AND IDENTIFICATION OF GLYPHOSATE RESISTANT, AMYLASE AND PROTEASE PRODUCING FUNGI FROM NON-AGRICULTURAL SOIL - U. I, HAMZA; M, KAILA; R, IBRAHIM; U. G, ALHASSAN; J. N, MOHAMMED (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Glyphosate herbicide is one of the most used herbicide throughout the world and they are very important to agriculture. Despite the role of herbicides to agriculture, they also posed direct or indirect threats to the health of humans and also to the nature and survival of soil microorganisms. However, there is a need for determination of the effect of herbicide on soil fungi. This research was carried out to determine the effect of glyphosate-base herbicide on the growth of soil fungi of non-agricultural soil of IBBUL Three sites of non-agricultural soil of IBBUL were selected and labelled as site (A, B and C) respectively. A serial dilution method and microscopic method were used for the isolation and identification of the different fungal species in the different soil treatments. A total of 270 isolates were identified and these comprises of thirteen genera namely, Aspergillus, Fusarium, Penicillium, Microsporum, Candida, Protostoma, Trichoderma, Xenosporella, Stylopage, Meria, Rhizopus, Papulospora, Paecilomyces. The frequency of fungi isolated showed that Aspergillus (33) had the highest occurrence followed by Fusarium (28), Stylopage (10) and Papulospora (12) in all the three sites (A, B and C). Aspergillus niger, Fusarium spp, Penicillium notatum, Microsporum spp, Candida albicans, Protostroma spp, Trichoderm spp, Xenosporella spp, Stylopage spp, Meria laricis, Rhizopus spp, Papulospora spp,and Paecilomyces spp were all amylase positive while others were amylase negative. Fusarium spp, Penicillium notatum, Microsporum spp, Candida albicans, Xenosporella spp, Stylopage spp, Rhizopus spp and paecilomyces spp were all protease positive while others were negative. This result indicates that the effect of glyphosate herbicide on the growth of soil fungi is not immediate. The result demonstrates overall negative effect of glyphosate on the growth of soil fungi. However, there is a need for long time studies on effect of glyphosate herbicide on the growth of soil fungi of non-agricultural and agricultural soil of IBBUL